Evaluation of oral cancer knowledge among dental students at the Federal University of Pernambuco, Brazil - Oliveira, Augusto César Pereira de (2025)
Objective: To evaluate the knowledge of oral cancer among dental students at the Federal University of Pernambuco, Brazil. Materials and methods: A cross-sectional study, in which a validated evaluation questionnaire was developed and administered to students via an interview invitation shared in virtual classrooms. Data were analyzed descriptively using inferential statistics, with a significance level of 5%. Results: A total of 212 students responded to the questionnaire: 70 from the first semester, 71 from the fifth semester, and 71 from the tenth semester. The majority were women (71.7%), with a mean age of 22.8 years. Conclusions: It was observed that students, especially those from the fifth and tenth semesters, despite having good theoretical knowledge of oral cancer and its main risk factors plus the ability to detect the disease during the clinical examination of patients, do not feel confident to perform diagnostic procedures such as biopsies. As a result, they refer patients to another professional.